Ethical hacking : networks and websites - Gupta, Sunil (Apress, 2018)
"Take the next step in enhancing your ethical hacking skills. Having completed the basic tutorial, you should have a firm grasp of the basics of ethical hacking. This course will cover key aspects of network and website security. After gaining a basic view of footprinting and vulnerability scanning with the basic video course, you will now dive deep into these concepts. Starting with setting up your own network penetration lab, you take a look network footprinting, where you will learn to scan your network for vulnerabilities. Following this, you will learn various techniques to exploit your network and perform penetration tests using Kali Linux. Shifting focus to websites, you will go through the key techniques of website footprinting and also see how to find vulnerabilities in your website, where you will work with examples of website exploitation. Finally, you will cover injection attacks, a common exploit technique used to detect flaws and breaches in websites."--Resource description page